Intersectionalities of Gender Violence: Legal Remedies: Editorial - Julie Goldscheid (Oñati Socio-Legal Series)
Critiques of legal remedies’ capacity adequately to address the intersectional nature of gender violence lie at the heart of both theoretical and practical discourse. Concern about remedies complements the important literature detailing the narrative experiences of those who experience violence grounded in multiple intersections of identity. This is an introduction to a set of papers that represent highlights from the conference entitled “International Congress on Gender Violence: Intersectionalities”. The papers address approaches to legal remedies that take into account the intersectional nature of gender violence.